Neisseria meningitidis ST-11 clonal complex bearing capsule serogroups B, C, or W in Brazil - Barroso, David E. (2013)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Bioquímica SIstemática. Rio de Janeiro, RJ, Brasil.